The Challenges and Opportunities of Public Governance in the Digital Era - Jin, Dandan (International Journal of Social Sciences and Public Administration, 2024)
In today’s digital age, public governance faces countless challenges and opportunities, and this article focuses on this research. Cybersecurity threats, digital divide, and regulatory issues pose significant challenges, while increased transparency, enhanced service delivery, and data-driven decision-making provide promising opportunities. By addressing these challenges and leveraging the opportunities brought by digital technology, governments can improve governance effectiveness, responsiveness, and public participation.